Understanding road accident injury dynamics in Iran: a growth mixture modelling perspective - Ziba Zarrin; Kamran Gholamizadeh; Elaheh Talebi-Ghane; Erfan Ayubi; Omid Hamidi (BMJ Open)
Objectives Road traffic injuries represent a significant public health concern globally. In Iran, road accidents have become a leading cause of death and disability, necessitating urgent attention to injury prevention strategies. This study aims to analyse the trends in injuries resulting from road accidents over a decade. Understanding these trends is crucial for informing targeted interventions and resource allocation, ultimately contributing to the reduction of road traffic injuries.Design Ecological study.Setting The data were obtained from the official database of the Iranian Legal Medicine Organization, which includes the injury rates of all provinces due to road accidents, from 2012 to 2021.Participants All records registered with injuries due to road traffic accidents across Iranian provinces.Outcome measures The incidence and average annual percentage of injury rates across provinces were illustrated using a map. A piecewise linear mixed-effects model was employed to estimate trends in injury rates, by gender. To identify distinct clusters of provinces exhibiting similar trends in injury rates, a growth mixture model was used over the 10 years.Results Among provinces, Qom (95% CI 18.99 to 37.21) and Sistan and Baluchestan (95% CI 5.41 to 7.66) had the highest and lowest injury rates over the decade, respectively. The annual rate of injuries in Iran increased by 0.52% from 2012 to 2018 and then gradually decreased by 1.16% after 2018. Four distinct classes were identified for the trend of injury rates over the decade: one cluster exhibited a significant decline, two clusters showed sharp increases and the last one had a steady trend.Conclusions These results contribute valuable insights into the dynamics of road accident-related injuries in Iran, offering a nuanced understanding of both overarching national trends and the unique patterns observed across provinces. Such knowledge can serve as a foundation for targeted interventions and policy formulations aimed at mitigating the impact of road accidents on public health and safety.